A reinvenção da existência: histórias de vidas e o confronto da proteção e desproteção social na realidade de Manaus/AM - Souza, Joselene Gomes de (2012)
This work is the result of qualitative research, based in oral histories and the understanding of the Brazilian social-historical context, its complexities and contrasts in the social relationships observed in daily practices of resistance to domination. The research aims at coming to an understanding of the subjects versions of the time periods and facts related to the Brazilian social protections during the 20th century, especially since the 1970 s. The work seeks to construct a trajectory starting with oral histories, with life narratives, mediated by memory and subjectivity, based on the life experiences of two women born in the city of Manaus in different decades. It presents a study that is detached from institutional discourse while at the same time values the memory, speech, individuality and subjectivity of real subjects and their forms of daily resistance, with the intention of contributing to the comprehension of the daily lives of children and adolescents in Brazil and the importance of social protections, particularly in Manaus, AM, which by nature finds itself mired in a political game, as well as reflecting on the Brazilian social protection system. It can be seen that a scenario permeated by social injustices which have constructed the history of thousands of people who struggle to validate equitable access to social protections. The study reveals the inefficiency of the State and the segmentation imposed by a capitalist society, mediated by the exclusion of access to goods and services, which constitute the challenges to making the Brazilian system of social protection, even when faced with recent advances